Ecomorphology of the Locomotor Apparatus in the Genus Cyrtodactylus (Gekkota, Squamata) - Jendrian Riedel; L. Lee Grismer; Timothy Higham; Joseph Wu; Quyen Hanh Do; Truong Quang Nguyen; Camila G. Meneses; Rafe M. Brown; Patrick D. Campbell; Thomas Ziegler; Anthony P. Russell; Dennis Rödder (Evolutionary Biology, 2024)
Adaptive radiations garner considerable interest from evolutionary biologists. Lizard radiations diversifying along structural niche space often exhibit distinct changes in body and limb proportions. One prediction is that terrestrial species inhabiting open habitats will have relatively longer hindlimbs, associated with faster running speeds, while scansorial species will have relatively shorter limbs to keep the centre of mass closer to the substratum. Alternatively, terrestrial species in densely vegetated habitats could benefit from relatively shorter limbs to prevent entanglement with more frequently encountered obstacles, whereas scansorial species could benefit from longer limbs promoting greater limb spans and static stability. Cyrtodactylus , an ecologically diverse gekkonid genus, includes numerous specialists with narrow structural niches, but the degree of morphological diversification exhibited by these specialists is largely unknown. We investigated associations between locomotor morphology and structural microhabitat use in Cyrtodactylus to test if either of the opposing predictions can be corroborated for this radiation. We measured body length and relative limb dimensions of 87 species, covering multiple independent transitions among structural microhabitat preferences. Using these data, we reconstructed the phylomorphospace and tested for associations between structural microhabitat niche and limb morphology. We found strong separation between structural niche groups in accordance with the second hypothesis, although overlap is evident among functionally related niches such as those of granite and karst specialists.

Pleistocene climatic fluctuations drive isolation and secondary contact in the red diamond rattlesnake ( Crotalus ruber ) in Baja California - Sean M. Harrington; Bradford D. Hollingsworth; Timothy E. Higham; Tod W. Reeder (Journal of Biogeography, 2018)
Aim Many studies have investigated the phylogeographic history of species on the Baja California Peninsula, and they often show one or more genetic breaks that are spatially concordant among many taxa. These phylogeographic breaks are commonly attributed to vicariance as a result of geological or climatic changes, followed by secondary contact when barriers are no longer present. We use restriction‐site associated DNA sequence data and a phylogeographic model selection approach to explicitly test the secondary contact hypothesis in the red diamond rattlesnake, Crotalus ruber . Location Baja California and Southern California. Methods We used phylogenetic and population clustering approaches to identify population structure. We then used coalescent methods to simultaneously estimate population parameters and test the fit of phylogeographic models to the data. We used ecological niche models to infer suitable habitat for C. ruber at the Last Glacial Maximum ( LGM ). Results Crotalus ruber is composed of distinct northern and southern populations with a boundary near the town of Loreto in Baja California Sur. A model of isolation followed by secondary contact provides the best fit to the data, with both divergence and contact occurring in the Pleistocene. We also identify a genomic signature of northern range expansion in the northern population, consistent with LGM niche models showing that the northern‐most portion of the range of C. ruber was not suitable habitat during the LGM . Main conclusions We provide the first explicitly model‐based test of the secondary contact model in Baja California and show that populations of C. ruber were isolated before coming back into contact near Loreto, a region that shows phylogeographic breaks for other taxa. Given the timing of divergence and contact, we suggest that climatic fluctuations have driven the observed phylogeographic structure observed in C. ruber and that they may have driven similar patterns in other taxa.

Springs, steroids, and slingshots: the roles of enhancers and constraints in animal movement - Timothy E. Higham; Duncan J. Irschick (Journal of Comparative Physiology B, 2013)